Karakoram in Transition : Culture, Development, and Ecology in The Hunza Valley - Edited by Kreutzmann, Hermann (Karachi Oxford University Press, 2006)
In the age of globalization the interconnectedness of world regions is perceived to a much higher degree than ever before. The remoteness of mountain areas has been converted into a view of mountains as a resource centre from where life-spending water originates, as an abode of pristine cultures, herbs, and niches. Pakistan incorporates some of the highest mountain regions, and the Karakorams have been one of the least known for many centuries. Here we find some of the steepest slopes, mass mobilization, earthquakes and the water towers of humankind. At the same time these areas are of geopolitical interest in boundary making and control. Trade routes of the caravan age have been transformed into motorable roads such as the Karakoram Highway. The impact of these changes are addressed in this book in which for the first time eminent scholars from various disciplines cooperate in an international effort to combine state of the art research results about the Hunza Valley. The academic interest in different aspects from culture, ecology, economy and development has been the starting point for presenting the Hunza Valley as an example of high mountain research from which new insights into sustainable mountain development can be derived. Therefore the focus on a specific valley opens methodological and conceptual venues based on sound empirical data from fieldwork experiences. The Hunza Valley can be considered as an arena of research and development for half a century. With this book the most recent insights are presented in a holistic effort.
Includes Colored Illustrations, Maps and Index
Keywords: Rural Development -- Asia--Karakoram Range